Problems and prospects of grapevine genetic resources preservation at “Magarach” Institute - A. A. Polulyakh; V. A. Volynkin; V. V. Likhovsko (Вавиловский журнал генетики и селекции, 2017)
Collection, preservation and effective use of grapevine genetic resources is vital for the development of ampelography as a subdiscipline of botany, for the successful development of industrial viticulture for contemporaries and future generations. The grapevine genetic resources of the Institute “Magarach” constitute one of the world’s oldest and richest ampelographic collections containing 4120 samples, of which 763 make a special selected collection and 3357 are in the base collection. The botanical diversity of the base collection is represented by three species of the genus Ampelopsis Michaux, two species of the genus Parthenocissus Planch., 22 species of the genus Vitis Linn., 612 varieties of interspecific origin, 2162 varieties of Vitis vinifera sativa D.C. and others. The specificity of preserving the field collection of grapevines – a culture that reproduces vegetatively – depends on the following factors: graft culture, perennial nature of the plants, genetic diversity of samples, which vary as to their resistance to biotic and abiotic environmental factors, and cultivation conditions. The successful establishment and conservation of future collections require fundamentally new cultivation techniques and application of cultivation methods involving revitalized grape planting stock. To supplement the traditional method of grapevine genetic resources conservation in the field collection, we have developed a method of preserving the gene pool collection in vitro under the minimal growth conditions. At the institute “Magarach” we have formed a vegetative collection of 40 grapevine varieties, hybrids and clones in vitro, and this work is under way. An effective way to solve the problem of gene pool preservation is cryopreservation, which is the main way of preserving genetic material of some crops. At present, the method of cryopreservation of the vine, considering the difficulties of overcoming the cryogenic damages of the biological material of grapes at ultra-low temperatures, remains the most difficult and chances of losing the collection are quite high. Thus, at present field collection is the main method of grape genetic resources conservation. Formation of in vitro grapevine collections method is considered a subsidiary one. In the future, it is expedient to develop methods for storing the plant material of grapes at ultra-low temperatures as a future technology.